Effect of listening to synchronous versus motivational music during warm-up on the diurnal variation of short-term maximal performance and subjective experiences - Belkhir, Y.; Rekik, G.; Chtourou, H.; Souissi, N. (Chronobiology International, 2020)
Which type of music is better for improving short-term maximal performance (STMP) and subjective experiences, and under what conditions? The present study was designed to address this issue by investigating the effects of listening to synchronous versus motivational music during warm-up, as a function of time of day, on exercise performance. In a random order, 16 highly trained physical education students (male) performed the 30-s Continuous Jump (CJ30) during six sessions separated at minimum by 48 h of recovery: after two warm-ups with synchronous music (WUSM), after two warm-ups with motivational music (WUMM), and after two warm-ups without music (WUWM), at 07:00 and 17:00 h. The maximal jump height (Hmax), mean jump height of all jumps (Hmean), and fatigue index (F %) were measured during the test. Body temperature was collected before and after the warm-up, and at the end of the CJ30 test. The rated perceived exertion (RPE) and the feelings states (FS) were obtained immediately after the warm-up and the test. The results revealed that Hmean, Hmax, and temperature were higher at 17:00 than 07:00 h in all experimental conditions. Moreover, Hmean and Hmax were higher with WUSM and WUMM than WUWM at both times of day, with greater improvement in the morning. After performing the CJ30 test, RPE scores were higher with WUMM than WUWM at both times of day. Moreover, FS scores were more positive with WUMM than WUWM in the morning. Furthermore, WUMM resulted in better Hmax and Hmean at both times of day than WUSM. However, FS and RPE were independent of types of music. Findings suggested the use of music during warm-up to increase STMP, RPE, and FS at both times of day, and reduce the morning-afternoon difference in the CJ30 test. More importantly, a warm-up with motivational music is more beneficial than a warm-up with synchronous music for improving STMP, either in the morning or in the afternoon.